Exploring the urban renewal strategy based on transit-oriented development concept--A case study of Japan and Hong Kong - Dai, Peng; Fu, Hui; Yang, Xuxu; Han, Song; Fu, Guannan; Wang, Yanjun (Frontiers in Materials, 2023)
In the wake of decreasing urban development space in China, urban regeneration has gradually changed from incremental renewal to stock renewal. Looking back on the past development process of urban renewal, we can find that “Transit-oriented Development” (TOD) plays an essential role in modern urban renewal. Therefore, in this study, we explain the concept and principles of TOD and discuss the logic of TOD and urban renewal. In addition, we summarize the basic features of urban renewal strategy based on the TOD concept through the analysis of TOD cases to provide some ideas for future urban renewal work.